The effects of implementing a gratitude development program on the quality of life and happiness of upper elementary school students - Erdeši, Josipa (Array, 2020)
The aim of this paper is to test the impact of the implementation of gratitude development program on the quality of life and happiness of sixth, seventh and eighth grade elementary school students. The total of 79 students of one elementary school from a rural part of Eastern Croatia participated in the research, divided into experimental (N = 39) and control (N = 40) groups. The gratitude development program was conducted once a day for a period of four weeks. The Personal Well-Being Index for School Children and the Subjective Happiness Scale were administered before and after the program. The results were processed by a two-way analysis of variance with repeated measurements on the first factor. There was a significant increase in the level of overall quality of life and specific quality of life domains in the experimental group in comparison to the control group. There were no significant changes in happiness level in the experimental group after the program. The findings contribute to a better understanding of the relationship of gratitude, the quality of life and the experience of happiness. Also, the results indicate the importance of using psychological interventions that can improve the quality of life of students in the educational context. The paper extensively discusses the usefulness of this research and its implications for future research.